Persistence in mutual funds performance: evidence from the Greek market - Mπαμπαλός, Βασίλειος (SPOUDAI Journal of Economics and Business, 2007)
The present study investigates the persistence hypothesis of Greek equity funds, during the period 1998-2004. We utilize all common performance measures and perform non-parametric tests. The results reveal weak evidence of persistence, which, however, disappears after 2001. Correctly adjusting for risk factors and documented portfolio strategies, explains a significant part of the previously reported persistence. JEL Classifications: G14, G15, G21, G23